Understanding the internet : a glimpse into the building blocks, applications, security and hidden secrets of the web - Curran, Kevin, 1969- (Chandos Publishing, 2009)
A straightforward overview with minimum technical descriptions of the underlying networking principles, standards, applications and uses of the Internet. Understanding the Internet explains the underlying networking concepts, the protocols and standards which comprise the Internet, Internet trends and applications, the mobile Internet, security and the hidden Web. The Internet and World Wide Web are dramatically changing the world we live in and this book provides a holistic view of the Internet so that practitioners and users can more fully understand the concepts involved.